Resiliensi Psikologis Sebagai Faktor Penentu dalam Hubungan antara Konflik Peran Ganda dan Komitmen Organisasional Wanita Pekerja di Kota Balikpapan - Pudjiati, Pudjiati; Aprianti, Dian Irma (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to analyze the role of psychological resilience in the relationship between dual role conflict and organizational commitment among working women in Balikpapan City. Using a quantitative approach, data were collected through questionnaires distributed to 150 female working respondents from various sectors. The analysis technique used SEM-PLS. The results indicate that dual role conflict has a significant negative effect on organizational commitment. However, psychological resilience has been shown to moderate this relationship, with individuals with high resilience able to maintain organizational commitment despite experiencing dual role conflict. Practical implications demonstrate the importance of organizational interventions to improve employee resilience, particularly among women.